KEY ASPECTS OF FINANCE MARKET SECTORS' INTEGRATION - Vladimir A. Slepov (Plekhanov Russian University of Economics, 2017)
The article discusses key aspects of finance market sectors' integration, which is caused by contradictory nature of the process for the economic system. The authors identify two groups of the said aspects. Firstly, it is identification criteria of finance market sectors' integration that embrace structural foundations of finance market functioning: its economic basis; the role and place in the process of GDP creation: dependence of market institutions on finance market functioning; conditionality of price dynamics in its segments; the nature of regulation on the part of state. Due to their identification it is possible to assess the key points of affecting the integration process on the part of finance market sectors in order to manage the process successfully. The authors came to the conclusion about the importance of monetary market as a central connecting link of integrated finance market. This link provides other segments of the finance market with liquidity, fixes temporary cash value, serves as a conductor of state regulation. Secondly, it is causes of integration process intensifying within the last decades. Their analysis allows us to find roots of the process, its actual and potential after-effects for high quality management of the process.